Assessment of the impact of DIAM interspinal dynamic stabilization on pain in the lumbar spine - the role of physiotherapy - Krzysztof Suszyński; Anna Dolińska; Dariusz Górka (Journal of Education, Health and Sport, 2023)
Pain in the LS segment occurs in both young and old people. Stabilization training is gaining more and more supporters in returning to proper functioning. Central stabilization is the ability to maintain the correct body posture during static and dynamic movements. The DIAM system of dynamic interspinal stabilization of the spine is a minimally invasive procedure which, by inserting a silicone implant between the spinous processes, relieves the intervertebral joints, the intervertebral disc and reduces the pressure on the nerve structures. Continuation after the procedure is systematic physiotherapy.